2021
DOI: 10.3390/ijms22042061
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Mutations and Expressions of Genes within the PI3K/Akt/mTOR Pathway in Breast Cancer—A Preliminary Study

Abstract: There is an urgent need to seek new molecular biomarkers helpful in diagnosing and treating breast cancer. In this elaboration, we performed a molecular analysis of mutations and expression of genes within the PI3K/Akt/mTOR pathway in patients with ductal breast cancer of various malignancy levels. We recognized significant correlations between the expression levels of the studied genes. We also performed a bioinformatics analysis of the data available on the international database TCGA and compared them with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…In the present study, the expression of the PIK3CA gene was upregulated in control adjacent tissue in comparison with breast carcinoma tissue. Similar results were also found in the studies performed by Kolodziej et al and Cizkova et al [ 55 , 56 ]. The lower expression was observed, possibly due to the correlation of expression with the normal group.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the expression of the PIK3CA gene was upregulated in control adjacent tissue in comparison with breast carcinoma tissue. Similar results were also found in the studies performed by Kolodziej et al and Cizkova et al [ 55 , 56 ]. The lower expression was observed, possibly due to the correlation of expression with the normal group.…”
Section: Discussionsupporting
confidence: 91%
“…The PI3K/AKT/mTOR complex is a central intracellular signaling pathway that controls essential cellular activities such as: cell metabolism, cell growth, cell proliferation, apoptosis, and angiogenesis (7). This signaling pathway consists of three main components including PI3K, AKT and mTOR (32). PI3Ks are an important family of plasma membrane-bound lipid enzymes that are activated by RTKs (receptor tyrosine kinase) and by GPCRs (G protein-coupled receptors) (17).…”
Section: Discussionmentioning
confidence: 99%
“…Multitargeting drugs have the potential advantage of eliciting synergistic effects, especially for cancer [ 43 ]. As targeted therapies have progressed, multiple PI3K/mTOR dual inhibitors have entered clinical trials and have shown good therapeutic effects [ 44 47 ]. We present evidence that taxifolin is a promising dual-targeting molecule that can inhibit both mTOR and PI3K.…”
Section: Discussionmentioning
confidence: 99%